СУБ’ЄКТ & СУСПІЛЬСТВО У СОЦІАЛЬНОМУ ПРОЕКТУВАННІ - Kleshnia, Hanna (Proceedings of the National Aviation University Series Philosophy Cultural, 2024)
Introduction. The world of the 21st century is changing, constantly and unpredictably. Changeable, dynamic, unstable, sometimes chaotic, the world is constantly challenging man and society. One of the ways to organize this spontaneous chaos is through social projecting. The aim is to make a philosophical reception of the role of the subject in social projecting through the prism of goal setting as a basic element of a social project. Research methods Social harmony as a goal of a social project is associated with economic and social prosperity, high material well-being and quality of life, but is not limited to them. A notable feature of social harmony is the high quality of the social and psychological climate in society and the social relations of classes and groups, as well as among individuals. Social harmony affirms the priority of the social sphere, which is directed, subordinated and coordinated by man. Research results. Social harmony as a goal of a social project is associated with economic and social prosperity, high material well-being and quality of life, but is not limited to them. A notable feature of social harmony is the high quality of the social and psychological climate in society and social relations among classes and groups, as well as among individuals. Social harmony affirms the priority of the social sphere, which is directed, subordinated and coordinated by man. Discussion. The concept of a person capable of living in the postmodern world is acquiring new characteristics. There is a shift from understanding the individual as a stable, structured system with a certain mechanism of development and interaction with the world, to the realization that the world is constructed here and now, and the "self" is constructed along with the world. According to F. Nietzsche, the human being, as a creative entity, is capable of changing their existence and, in this creative beginning, becomes akin to God; however, they also become part of the general chaos of being. In the process, all of humanity’s achievements in philosophy, science, and ultimately in culture as a whole, are leveled. Conclusions. In the process of philosophically understanding the change in the role of the subject and society as the basis for goal setting in social projecting, we discover a certain correlation with the axiological principles of a specific cultural and historical epoch. Unlike the social project of modernity, the postmodern social project is a social rhizome, consisting of a chaotic diversity of individual and social practices, which in their dichotomous unity form a complex palette of society and individual self-realization.